The Usefulness of Adopting the Last Planner System in the Construction Process of Addis Ababa Road Projects - Zenawi Mehari Limenih; Belachew Asteray Demisse; Abenezer Tariku Haile (Advances in Civil Engineering)
Addis Ababa road construction projects fail to be executed on time, within the allocated budget, and with the desired quality. To solve this problem, a new management concept is introduced, namely, lean construction. It is known to increase productivity and minimize waste. And, to realize this solution, last planner system (LPS) is used; it is a tool of lean construction and it involves a person or group of people with the task to control the production unit. The objectives of this study are to examine the current construction process management practice in Addis Ababa city road construction projects, to identify and prioritize the expected barriers of the last planner system implementation in Addis Ababa road construction projects using the super decision model, to identify and prioritize last planner system implementation benefits to Addis Ababa road construction projects using the super decision model, and to develop a conceptual framework for the last planner system implementation to enhance the current construction management system in Addis Ababa city road construction projects. To address the problems, questioners, observations, interviews, focus group discussions, and recently published journals were employed as qualitative and quantitative data collection tools and analyzed using statistical package for the social science version 26 and super decision model version 3.2. The finding shows that the construction management process adopted in all three sites is more or less similar, as they use a push planning system and critical path method to determine the duration following the master schedule but have no weekly work plan and lookahead schedule to forecast the coming week’s duty; also, they use a push planning system, for materials. The LPS implementation expected barriers are also ranked from one to five: Labor related, internal working environment related, stakeholders related, exogenous related, and material related expected barriers, respectively. The last planner system has many benefits as agreed by different scholar. Time-related, cost-related, claim-related, and quality-related benefits are the main benefits obtained through the LPS implementation, and it is possible to conclude that LPS is useful for road construction management process. Moreover, the LPS implementation conceptual framework was also developed based on the last planner system principles.